Interactionism of private education sector: business model innovation in the selected tuition centres in Malaysia - Siti Som Husin (2022)
The small and medium-sized enterprises (SMEs) that is failing in the industry keeps increasing. This is due to the continual contextual challenges that SMEs face, such as those within the dimensions of technology, finance, and culture. As these challenges force SMEs to adopt changes for survival and sustainability, their business model could not be stagnant. SMEs should be sensitive to contextual changes and innovate. Hence, the phenomenon of business model innovation (BMI) should be understood well. Otherwise, unreliable BMI will hamper SMEs’ growth. To understand the phenomenon, SMEs’ current practices in BMI should be investigated. Previous studies focusing on BMI have explored the phenomenon through the economics lens, such as studying product innovation as a source of revenue stream. However, little is known about understanding BMI through the interactionist perspective. The interactionism viewpoint is significant because it unfolds a phenomenon based on the meaning-making process through the interaction of self, society, and the environment. Therefore, the main objective of this study is to explore the SMEs’ BMI practises to understand the phenomenon through the lens of interactionism. This study utilises interpretivism as a research paradigm along with an abductive case study strategy. Informants were from SMEs in the private education sector. Three SMEs were involved in this study with 29 in-depth interviews conducted with the founder, business partner, teacher, and student. Data for this study comes from in-depth interviews, direct observation, and documents. The primary data source comes from in-depth interview transcripts. Once collected, the primary data were analysed manually using narrative and dramaturgical coding to reveal the thematic narrative. Other data sources were used as evidence to increase research reliability. The symbolic interactionism theory’s premises provided the theoretical underpinning for this study. The study unveiled three thematic narratives concerning the phenomenon of BMI. The first narrative is about ‘The Killer Teacher’, followed by ‘Digital Survivor', and ‘The Influencer Persona’. Each narrative stands were present in the three episodes. The Triadic Model was also utilised to increase the understanding of SME business model innovation within the context of the private education industry. This new knowledge will help other entrepreneurs and their teams, especially in this particular industry, develop an innovative business model for strategic purposes to ensure their SME's growth. Hence, this study also contributes to entrepreneurial research by offering new perspectives on theoretical and methodological contributions, such as symbolic interactionism theory and case study abductive method. Future research could focus on other industries and several geographical areas as potentially unique and interesting findings may help increase the understanding of the phenomenon and lead to better practices.